Eco-Innovation on the Cost of Equity and Financial Performance: The Moderating Role of Ownership Structure - Leliana, L; Carolina, Yenni (Universitas Pendidikan Indonesia, 2024)
This study aims to examine the effect of eco-innovation on the cost of equity and financial performance moderated by ownership structure. This study uses quantitative methods, and data is analyzed using panel data analysis with Eviews. Samples obtained were 237 companies from companies listed on the Indonesia Stock Exchange period 2017-2020. The results show eco-innovation does not affect the cost of equity because the issue of eco-innovation has not become a crucial issue in public; eco-innovation hurts financial performance because of significant expenses for implementation. Ownership structure does not affect eco-innovation, meaning shareholders cannot intervene in the implementation of eco-innovation. Ownership structure (managerial, family, institutional, foreign) harms the cost of equity while ownership structure (government) has a positive impact on the cost of equity. Ownership structure has a negative effect on financial performance because of conflict of interest between shareholders and management, ownership structure does not moderate the relationship between eco-innovation and cost of equity or financial performance because the ownership structure in this research tends not to change. The implications are addressed to investors, company, and future researchers. The implications also need government support in socializing the importance of eco-innovation so investors are more observant in investing. The ownership structure consists of managerial, institutional, family, government, and foreign ownership structures, which are used as moderating variables and independent variables. The five types of ownership structures are examined at once.